PENYUSUTAN BOBOT BADAN DAN FREKUENSI RESPIRASI SAPI MADURASETELAH MENEMPUH PERJALANAN DENGAN LAMA WAKTU YANG BERBEDA - Nugroho, Fauzan Anggi; Yuwono, Pambudi; Setyaningrum, Agustinah (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Backgrund. This study aims to determine the loss of body weight and respiration frequency of Madura cattle after traveling for different lengths of time. Materials and Methods. The material used in this study were 45 Madura cattle that had traveled through different distances. The method used in this research was survey. The research variables were consisted of Body Weight Before Delivery, Arrival Body Weight, Depreciation Body Weight and Respiration Frequency. Data were analysed using descriptive analysis and variance analysis to determine whether there was an influence of travel time on body weight and respiration frequency of Madura cattle. Results. The average weight loss of Madura cattle after traveling with different lengths of time were W1 (5-10 hours) of 5.17±1.34%, W2 (>10-15 hours) of 8.19±1.20% and W3 (>15-20 hours) in the amount of 12.19±2.88%. After BNJ test, different results were obtained for the value of depreciation, namely W1 (5-10 hours) of 13.05±1.69%, W2 (> 10-15 hours) of 16.52±2.09% and W3 (>15-20 hours) at 20.30±2.50% .Based on the results of the Variance test showed that the weight loss of Madura cattle after traveling with a different travel time had a very significant effect (P<0.01) on body weight loss. The average frequency of Madura cattle respiration after traveling with different lengths of time were W1 (5-10 hours) of 29.9±1.5 times/minute, W2 (>10-15 hours) of 30.8 ± 2.0 times/minute and W3 (>15-20 hour) of 30.9±1.5 times/minute. Based on the variance test results obtained which significance value (P>0.05) means that there was no significance influence of travel time on the frequency of respiration. Conclusion. In conclusion this is longer travel time during shipping, higher the weight loss of Madura cattle.